2021
DOI: 10.3390/ijms23010417
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Signature and Involvement in Chronic Rhinosinusitis with Nasal Polyps

Abstract: Cytokines are well known to play a central role in chronic rhinosinusitis with nasal polyps (CRSwNP), particularly in maintenance of the inflammatory response and the recruitment of eosinophils. The pathophysiological concepts concerning the involvement of inflammatory cytokines in CRSwNP have gradually evolved. Although the Th2 cytokines environment associated with an eosinophilic infiltration has retained a central role in the genesis of polyps, the role of other cytokine subpopulations has also and more rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 120 publications
(135 reference statements)
0
23
0
Order By: Relevance
“…Consistently, MPO in neutrophils and, to a lesser extent, in monocytes [ 43 ] also derives reactive oxidant hypochlorous acid (HOCl), playing an important role in neutrophil antimicrobial activity and human defense [ 43 , 44 ]. It was reported that the dense inflammatory infiltrate of the typical histological features of NPs is composed of several immune cell types, such as T and B lymphocytes, group 2 innate lymphoid cells, eosinophils and neutrophils, mast cells, and macrophages [ 45 ]. Thus, it was supposed that MPO should be upregulated in CRSwNP NPs.…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, MPO in neutrophils and, to a lesser extent, in monocytes [ 43 ] also derives reactive oxidant hypochlorous acid (HOCl), playing an important role in neutrophil antimicrobial activity and human defense [ 43 , 44 ]. It was reported that the dense inflammatory infiltrate of the typical histological features of NPs is composed of several immune cell types, such as T and B lymphocytes, group 2 innate lymphoid cells, eosinophils and neutrophils, mast cells, and macrophages [ 45 ]. Thus, it was supposed that MPO should be upregulated in CRSwNP NPs.…”
Section: Discussionmentioning
confidence: 99%
“…It was well demonstrated that increased IgE and IL-8 concentrations may be found in patients with CRSwNP stimulating multiple inflammatory pathways [ 23 , 24 ]. Indeed, IL-8 plays a crucial role in the inflammatory processes acting as a chemotactic factor for neutrophils and lymphocytes, as angiogenic factor, as well as tumor progression [ 25 , 26 , 27 ], and an IL-8-dominant inflammatory profile is frequently found in patients with CRSwNP [ 28 , 29 ]. Since patients showed a clear improvement in both clinical stage and quality of life after dupilumab treatment accompanied by a reduction in IL-8 concentration, this evidence confirms, for the first time, the downstream action of dupilumab on IgE and IL-8, which led to the amelioration of the inflammatory status and to counteract the CRSwNP progression.…”
Section: Discussionmentioning
confidence: 99%
“…Most CRSwNP is characterized by type 2 inflammation, which is defined as an adaptive immune response with Th2 cells driving eosinophil recruitment and IgE production through the secretion of type 2 cytokines such as IL-4, IL-5, and IL-13. [17][18][19] The dramatic clinical responses common to dupilumab could lead to not only changes in the type 2 inflammatory environment within the sinonasal mucosa and nasal polyp, but also directly and/or indirectly affect the systemic immune status. The objective of this study was to analyze circulating immune cells, particularly T cells, in CRSwNP patients treated with dupilumab.…”
Section: Discussionmentioning
confidence: 99%